Highly stretchable and tough alginate-based cyclodextrin/Azo-polyacrylamide interpenetrating network hydrogel with self-healing properties. (15th March 2021) - He, Furui; Wang, Longzheng; Yang, Shujuan; Qin, Wenqi; Feng, Yuhong; Liu, Yuanyuan; Zhou, Yang; Yu, Gaobo; Li, Jiacheng
Graphical abstract: Highlights: A highly stretchable and tough composited hydrogel was proposed with self-healing property. Alginate-based cyclodextrin was obtained through the Ugi condensation. The reversible sol-gel transformation was photocontrollable. Self-healing behavior can be achieved by light irradiation. Abstract: Most structural self-healing materials were developed based on either reversible supramolecular interaction or dynamic covalent bonding. It seems a good idea to incorporate self-healing properties into high-performance materials. In this study, we fabricated the alginate-based cyclodextrin and polyacrylamide azobenzene highly stretchable and tough interpenetrating composite hydrogel with self-repairing behavior under light irradiation. Initially, the alginate-based cyclodextrin and polyacrylamide azobenzene were designed and synthesized. The corresponding structural, thermal, and morphological properties of hydrogels were characterized. The reversible transformation of the sol-gel can be achieved by the irradiation upon ultraviolet light and visible light. The self-healing behavior of this composited gel is based on the host-guest interaction between cyclodextrin and azobenzene. The recovery gel elongation at 48 h healing in the dark condition was is 0.04 MPa, with an elongation of 1140 %. Therefore, this gel can achieve self-healing ability while maintaining highly stretchable and tough performance.